'A Strong, Brown God': T.S. Eliot's Mississippi River Exploration of the White Atlantic. (2nd January 2021) - Palmer, William C.
ABSTRACT: T.S. Eliot opens 'The Dry Salvages, ' the third of his Four Quartets with a speaker stating the belief that 'the river/Is a strong brown god, sullen, untamed, intractable' (1–2). This article begins with follow-up questions: where and who is the brown god and how do Eliot and his speakers situate themselves in the new geography of a breaking world? Through geographical consideration, biographical knowledge, historical context, and formal analysis, this essay posits the Mississippi River as Eliot's stated brown god and considers the historical and philosophical implications of what it means for the paragon Anglo-American expatriate to return to the river of his youth in the final grand poetic effort of his literary career. Four Quartets goes back in time and space shifts across impossible geographies. In the poem, Eliot attempts and fails to understand African American life in white modernity at the same time he uses the Mississippi to exist within the Atlantic Ocean. He and his speakers spend their poetic time trying to become a universal poetic voice in a new modern existence and falling short.